Plasma Metabolomics Reveals Dysregulated Metabolic Signatures in HIV-Associated Immune Reconstitution Inflammatory Syndrome - Pei, Luxin; Fukutani, Kiyoshi F.; Tibúrcio, Rafael; Rupert, Adam; Dahlstrom, Eric W.; Galindo, Frances; Laidlaw, Elizabeth; Lisco, Andrea; Manion, Maura; Andrade, Bruno B.; Sereti, Irini (Frontiers in Immunology, 2021)
Immune reconstitution inflammatory syndrome (IRIS) is an inflammatory complication associated with an underlying opportunistic infection that can be observed in HIV-infected individuals shortly after the initiation of antiretroviral therapy, despite successful suppression of HIV viral load and CD4+ T cell recovery. Better understanding of IRIS pathogenesis would allow for targeted prevention and therapeutic approaches. In this study, we sought to evaluate the metabolic perturbations in IRIS across longitudinal time points using an unbiased plasma metabolomics approach as well as integrated analyses to include plasma inflammatory biomarker profile and whole blood transcriptome. We found that many lipid and amino acid metabolites differentiated IRIS from non-IRIS conditions prior to antiretroviral therapy and during the IRIS event, implicating the association between oxidative stress, tryptophan pathway, and lipid mediated signaling and the development of IRIS. Lipid and amino acid metabolic pathways also significantly correlated with inflammatory biomarkers such as IL-12p70 and IL-8 at the IRIS event, indicating the role of cellular metabolism on cell type specific immune activation during the IRIS episode and in turn the impact of immune activation on cellular metabolism. In conclusion, we defined the metabolic profile of IRIS and revealed that perturbations in metabolism may predispose HIV-infected individuals to IRIS development and contribute to the inflammatory manifestations during the IRIS event. Furthermore, our findings expanded our current understanding IRIS pathogenesis and highlighted the significance of lipid and amino acid metabolism in inflammatory complications.